Pemilihan Vegetasi terhadap Kriteria Ruang Terbuka Stadion di Jakarta International Stadium - Pawitra Sari; Retno Fitri Astuti; Desta Promesetiyo Bomo (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
The stadium open space at JIS has the concept of sustainable landscape by considering ecological, aesthetic, and social aspects. This study’s goal is to identify several vegetative traits that meet the standard deviation of the area being studied. This study's methodology consists of qualitative analysis based on related literature research of the type, function, and layout of vegetation with case studies of stadium open spaces. The results show that the selection of ecologically functioning vegetation dominates in JIS. Vegetation for social functions close to seating and architectural functions lies in harmony with the shape of the composition of the building mass with the shape of the tree canopy that embodies building performance. The use of grass is ecologically intended for water catchment because JIS has a zero run off concept. Vegetation selection and replanting of relocation trees with adaptive planning to the location and conditions of JIS and low maintenance as well as to meet the green-based area in the green building concept